2013
DOI: 10.1080/10803548.2013.11076981
|View full text |Cite
|
Sign up to set email alerts
|

Performance on a Work-Simulating Firefighter Test Versus Approved Laboratory Tests for Firefighters and Applicants

Abstract: Aim. Firefighters must meet minimum physical demands. The Norwegian Labour Inspection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 30 publications
(59 reference statements)
2
50
0
1
Order By: Relevance
“…The results of this study suggest that the Trondheim test could be used to examine adequate physical fitness of professional firefighters. A parallel study has shown that physically fit recruits perform as well as experienced fire fighters on this test [46]. That is a further advantage of this work-simulating test.…”
Section: Work-simulated Tests or Laboratorymentioning
confidence: 71%
“…The results of this study suggest that the Trondheim test could be used to examine adequate physical fitness of professional firefighters. A parallel study has shown that physically fit recruits perform as well as experienced fire fighters on this test [46]. That is a further advantage of this work-simulating test.…”
Section: Work-simulated Tests or Laboratorymentioning
confidence: 71%
“…Perhaps one of the superior tests that considers the effects of the work environment on physical capability and job performance is the Trondheim test, developed by the Trondheim Fire Brigade in Norway for firefighter applicants (von Heimburg and Medbo 2013;von Heimburg et al 2013). The test, which was designed to assess physical capabilities specific to firefighting, requires participants to complete several firefighting task in 3 parts.…”
Section: Firefightingmentioning
confidence: 99%
“…Applicants must complete the entire test battery in 19 min or less to pass. It is, however, noteworthy that this proposed standard has yet to be verified (von Heimburg et al 2013). Furthermore, this test may require further enhancement as it was found to be less predictive of muscular fitness (von Heimburg et al 2013).…”
Section: Firefightingmentioning
confidence: 99%
“…Weak to moderate (but significant) correlations have been observed with combined task simulations lasting between 5 and 10 minutes in U.S (r = -0.38) (Williford et al, 1999) and Norwegian (r = -0.53) firefighters (Von Heimburg, Rasmussen, & Medbo, 2006). Cardiorespiratory fitness exhibits the strongest associations with firefighting simulations lasting approximately 10 minutes (r 2 = 0.57) (Williams-Bell, Villar, Sharratt, & Hughson, 2009) or longer (r = -0.72) (Von Heimburg, Medbo, Sandsund, & Reinertsen, 2013), supporting the notion that cardiorespiratory fitness is an important determinant of task performance during sustained tasks.…”
Section: Introductionmentioning
confidence: 99%